Education on children's dental health through illustrated books based on local wisdom in Probolinggo District - Sinaredi, Betadion Rizki; Bramantoro, Taufan; Firmansyah, Fikri Febrian; Cahyaningtyas, Carissa Putri; Firdausi, Nurul Layly (Indonesian Journal of Dental Medicine, 2023)
Background: Dental problems are health problems that have to be taken into account, especially in Indonesia, where it is known that the correct brushing time for Indonesian people is only 2.8%. Meanwhile, in the working area of the Dringu Health Center in Probolinggo Regency, East Java, Indonesia the prevalence of dental caries in Taman Sari Village reached 46%. Purpose: This study aims to determine the knowledge of Pos Layanan Terpadu/Posyandu (Integrated Service Post)cadres from the socialization of children's dental health illustration books activities with local languages in the working area of the Dringu Health Center, Probolinggo Regency, East Java, Indonesia. Methods: This activity is a socialization for children's dental health illustration books using the Madurese language, involving cadres and staff of the Dringu Health Center, Probolinggo Regency, East Java, Indonesia. The increased knowledge of the participants is assessed through the results of the pre-test and post-test that have been done. Results: The results showed that there was an increase in participants knowledge by 21%. Conclusion: The socialization of dental health illustration books in local languages in the working area of the Dringu Health Center, Probolinggo Regency, East Java, Indonesia can increase participants knowledge about dental health.